2023
DOI: 10.1136/bmjdrc-2022-003136
|View full text |Cite
|
Sign up to set email alerts
|

Association between integrase strand transfer inhibitor use with insulin resistance and incident diabetes mellitus in persons living with HIV: a systematic review and meta-analysis

Abstract: Whether integrase strand transfer inhibitors (INSTIs) are associated with a higher risk of incident type 2 diabetes mellitus (DM) than other antiretroviral therapies (ART) needs to be established.MEDLINE, Embase, Web of Science, and ClinicalTrials.gov registries were searched for studies published between 1 January 2000 and 15 June 2022. Eligible studies reported incident DM or mean changes in insulin resistance measured by Homeostatic Model for Insulin Resistance (HOMA-IR) in patients on INSTIs compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
(315 reference statements)
0
13
0
Order By: Relevance
“…In an earlier meta-analysis evaluating the association of INSTI use with incident diabetes mellitus, we demonstrated reduced risk in comparison to NNRTIs and protease inhibitors (PIs) apart from African populations where the risk was threefold increased [39]. These results have been replicated in another published meta-analysis [40].…”
Section: Studies Inmentioning
confidence: 52%
“…In an earlier meta-analysis evaluating the association of INSTI use with incident diabetes mellitus, we demonstrated reduced risk in comparison to NNRTIs and protease inhibitors (PIs) apart from African populations where the risk was threefold increased [39]. These results have been replicated in another published meta-analysis [40].…”
Section: Studies Inmentioning
confidence: 52%
“…Review of current suggests that at population level, integrase inhibitors are associated with a reduced risk of incident diabetes mellitus compared to NNRTIs and PIs [1], [2]. There is also evidence to demonstrate insigni cant differences in effects on insulin resistance compared to other HIV drug classes [2].…”
Section: Discussionmentioning
confidence: 99%
“…Review of current suggests that at population level, integrase inhibitors are associated with a reduced risk of incident diabetes mellitus compared to NNRTIs and PIs [1], [2]. There is also evidence to demonstrate insigni cant differences in effects on insulin resistance compared to other HIV drug classes [2]. Additionally, there are published case reports documenting that a certain section of heavily ART experienced PWH, probably with a currently unclear predisposition develop accelerated hyperglycemia when exposed to integrase inhibitors[3]- [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis of 13 randomized controlled trials and six observational cohort studies has shown no significant increase in the risk of Type 2 diabetes for people taking integrase inhibitors [32]. The most commonly reported endpoint was fasting hyperglycemia of at least Grade 2, or HbA1C above 6.5%.…”
Section: Risks Of Diabetes From Integrase Inhibitor Usementioning
confidence: 99%